2014
DOI: 10.1002/qj.2456
|View full text |Cite
|
Sign up to set email alerts
|

Response of the large‐scale structure of the atmosphere to global warming

Abstract: This paper discusses the possible response of the large-scale atmospheric structure to a warmer climate. Using integrations from the fifth phase of the Coupled Model Intercomparison Project (CMIP5) in conjunction with physical arguments, we try to identify what changes are likely to be robust and what the underlying mechanisms might be. We focus on the large-scale zonallyaveraged circulation, in particular on height of the tropopause, the strength and position of the surface westerlies and the strength and ext… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

39
266
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 256 publications
(308 citation statements)
references
References 90 publications
39
266
3
Order By: Relevance
“…Research of this kind contains particular relevance when considering the implications of global climate change [57]. For example, the effect of climate change on seasonal patterns of atmospheric circulation over the Gulf of Mexico [58] or North Atlantic [59] may create additional costs or hazards during transoceanic migration. Climate change may also alter the quality of ecological resources on the breeding grounds through the influence of mid-latitude climate extremes [60] or on the wintering grounds through the influence of global warming [61].…”
Section: Discussionmentioning
confidence: 99%
“…Research of this kind contains particular relevance when considering the implications of global climate change [57]. For example, the effect of climate change on seasonal patterns of atmospheric circulation over the Gulf of Mexico [58] or North Atlantic [59] may create additional costs or hazards during transoceanic migration. Climate change may also alter the quality of ecological resources on the breeding grounds through the influence of mid-latitude climate extremes [60] or on the wintering grounds through the influence of global warming [61].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have begun to bridge this gap by examining the response of comprehensive models to idealized and more realistic greenhouse gas forcings. While Grise and Polvani (2014) found evidence that Southern Hemisphere Hadley cell expansion scales with climate sensitivity, Vallis et al (2015) found little relationship between the transient climate response and Hadley cell expansion. Studies have also found evidence of a seasonality (Polvani et al, 2011b) and a lack of seasonality (McLandress et al, 2011) in Southern Hemisphere expansion.…”
Section: Introductionmentioning
confidence: 98%
“…The strengthening of these thermal winds occurs because, despite polar amplification of warming in the lower troposphere, increased carbon dioxide (CO 2 ) is enhancing the column-averaged pole-to-equator temperature gradient in the midlatitudes, through the combined effect of tropospheric warming and stratospheric cooling (Shine et al, 2003;Delcambre et al, 2013;Goessling and Bathiany, 2016). The increase in the magnitude of the meridional temperature gradient at aircraft cruising altitudes stems from robust thermodynamic effects and is unlikely to be significantly abated by feedbacks from the dynamics (Vallis et al, 2015). In the lower troposphere, the result of the temperature changes is weaker zonal winds, which may cause more extreme weather (Francis and Vavrus, 2012).…”
Section: Introductionmentioning
confidence: 99%